Modelagem de nicho ecológico de Neoseiulus californicus McGregor E Neoseiulus idaeus Denmark & Muma dois importantes inimigos naturais de Tetranychus urticae Koch - Araújo, Jackson de Lima (2019)
Predator mites of the Phytoseiidae family are the main agents of biological control of pest mites in the world, especially those of the genus Neoseiulus and particularly the species Neoseiulus californicus and Neoseiulus idaeus. Among the targets of these natural enemies is the mite Tetranychus urticae. One of the factors related to unsuccessful use of natural enemies in biological control programs is the non-compatibility of the control agent with the climatic conditions of the site of release. Based on the climatic requirements of N. californicus and N. idaeus, this study aimed to predict geographical areas with potential for the establishment of both species of predator, to allow inferring which of them is indicated to be used in a program of biological control of pests of a certain locality. Sites of occurrence and environmental variables were obtained from pre-existing spatial information found in online databases and the models were generated with MAXENT software. The results of the present study demonstrate that: (i) N. californicus and N. idaeus are able to establish in distinct sites in the different continents; (ii) the probability of establishment for N. californicus was especially limited by conditions of high temperatures, whereas for N. idaeus the limitations were conditions of annual variation of temperatures. These results may help choosing one of these predators as biological control agent in a certain area.